Comparative analysis of nuclear, chloroplast, and mitochondrial genomes of watermelon and melon provides evidence of gene transfer - Cui, Haonan (Sci Rep, 2021)
During plant evolution, there is genetic communication between organelle and nuclear genomes. A comparative analysis was performed on the organelle and nuclear genomes of the watermelon and melon. In the watermelon, chloroplast-derived sequences accounted for 7.6% of the total length of the mitochondrial genome. In the melon, chloroplast-derived sequences accounted for approximately 2.73% of the total mitochondrial genome. In watermelon and melon, the chloroplast-derived small-fragment sequences are either a subset of large-fragment sequences or appeared multiple times in the mitochondrial genome, indicating that these fragments may have undergone multiple independent migration integrations or emerged in the mitochondrial genome after migration, replication, and reorganization. There was no evidence of migration from the mitochondria to chloroplast genome. A sequence with a total length of about 73 kb (47%) in the watermelon chloroplast genome was homologous to a sequence of about 313 kb in the nuclear genome. About 33% of sequences in the watermelon mitochondrial genome was homologous with a 260 kb sequence in the nuclear genome. A sequence with a total length of about 38 kb (25%) in the melon chloroplast genome was homologous with 461 sequences in the nuclear genome, with a total length of about 301 kb. A 3.4 Mb sequence in the nuclear genome was homologous with a melon mitochondrial sequence. These results indicate that, during the evolution of watermelon and melon, a large amount of genetic material was exchanged between the nuclear genome and the two organelle genomes in the cytoplasm.